DEVELOPMENT OF CANVA-BASED MATHEMATICS LEARNING MEDIA ON NUMBER PATTERN MATERIAL - Leony Eriani Johanis; Bakher Nenotaek (Mandalika Mathematics and Educations Journal, 2026)
This research is a research and development (R&D) project that aims to produce a Canva-based interactive learning media entitled "POLANDIA: Number Patterns in Mathematics" on the Number Patterns material for eighth-grade junior high school students and to test its effectiveness in improving student learning outcomes. The development model used is ADDIE, which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of the study were eighth-grade junior high school students who were involved in the limited trial and field trial stages. The learning media were designed with attractive visual displays, interactive animations, and Google Form-based evaluation quizzes to help students understand the abstract concept of Number Patterns. Data collection techniques included learning outcome tests, student response questionnaires, and expert validation sheets. Data were analyzed descriptively, quantitatively, and qualitatively. The results showed that the "POLANDIA" learning media was effective in use, as indicated by a classical learning completion rate of 92.86%, as well as positive student responses to its use. Thus, the Canva-based interactive learning media "POLANDIA" can be an innovative and effective alternative in digital mathematics learning at the junior high school level.